2015
DOI: 10.1111/azo.12139
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structures of the ovary and female genital ducts of Supachai's caecilian, Ichthyophis supachaii Taylor, 1960 (Amphibia: Gymnophiona)

Abstract: Pewhom, A., Chumnanpuen, P., Muikham, I., Chatchavalvanich, K. and Srakaew, N. 2015. Microscopic structures of the ovary and female genital ducts of Supachai's caecilian, Ichthyophis supachaii Taylor, 1960 (Amphibia: Gymnophiona). -Acta Zoologica (Stockholm) 00: 000-000.The structures of the female reproductive system (ovary, oviduct and cloaca) of Ichthyophis supachaii were investigated by dissection, histology and light microscopy. Paired, elongated, sac-like ovaries are parallel to the gut and fat bodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Mucosubstances are present throughout the digestive tract of I. supachaii from the oral cavity to the intestine, as described in this study, and in the cloaca, as reported in previous studies (Pewhom et al 2015(Pewhom et al , 2016. The distribution patterns of glycoconjugates along the digestive tract of I. supachaii exhibit regional variation and possibly interspecific variation, compared to other caecilians, including I. glutinosus (Zylberberg 1977), Caecilia gracilis, H. rostratus, M. unicolor, T. compressicauda (Exbrayat 1996(Exbrayat , 2003, S. annulatus (Junqueira et al 1999) and I. cf.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Mucosubstances are present throughout the digestive tract of I. supachaii from the oral cavity to the intestine, as described in this study, and in the cloaca, as reported in previous studies (Pewhom et al 2015(Pewhom et al , 2016. The distribution patterns of glycoconjugates along the digestive tract of I. supachaii exhibit regional variation and possibly interspecific variation, compared to other caecilians, including I. glutinosus (Zylberberg 1977), Caecilia gracilis, H. rostratus, M. unicolor, T. compressicauda (Exbrayat 1996(Exbrayat , 2003, S. annulatus (Junqueira et al 1999) and I. cf.…”
Section: Discussionsupporting
confidence: 86%
“…While the oesophageal longitudinal folds and gastric rugae do not seem to alter the total surface areas of the oesophagus and the stomach, respectively, the intestinal folds increase the intestinal surface areas for enzymatic digestion and nutrient absorption, like the mammalian intestinal villi (Ross and Pawlina 2015). However, the intestinal folds of I. supachaii are structurally different from the avian and mammalian villi of which the lamina propria possesses the central lacteal and the base leads into the intestinal tubular glands (crypts of Lieberk€ uhn; Andrew and Hickman 1974;Ishikawa et al 1985;Chikilian and de Speroni 1996;Reynolds and Rommel 1996;Zaher et al 2012) Mucosubstances are present throughout the digestive tract of I. supachaii from the oral cavity to the intestine, as described in this study, and in the cloaca, as reported in previous studies (Pewhom et al 2015(Pewhom et al , 2016. The distribution patterns of glycoconjugates along the digestive tract of I. supachaii exhibit regional variation and possibly interspecific variation, compared to other caecilians, including I. glutinosus (Zylberberg 1977), Caecilia gracilis, H. rostratus, M. unicolor, T. compressicauda (Exbrayat 1996(Exbrayat , 2003 (Zylberberg 1977), Hyla japonica, Pelophylax nigromaculatus (formerly Rana nigromaculata), Xenopus laevis (Suganuma et al 1981), R. aurora aurora (Ferri et al 2001), P. viridis and Rana temporaria (Liquori et al 2002) and Rhinella icterica (Machado-Santos et al 2014); and urodeles, including Calotriton asper (formerly Euproctus asper), Lissotriton helveticus, Pleurodeles waltii, Salamandra salamandra, Triturus cristatus, T. marmoratus (Zylberberg 1977), Ambystoma mexicanum (Suganuma et al 1981) and T. carnifex (Liquori et al 2007).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In Ch. indistinctum (Berois, De Sa, 1988) and I. supachai (Pewhom et al, 2015), germinal nests are randomly scattered throughout entire ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The first descriptions of the female reproductive tract in Gymnophiona were provided by Müller (1832) and Rathke (1852). There have been an increasing number of studies describing the anatomy of the reproductive systems of caecilians including both phylogenetically basal oviparous [Ichthyophis supachaii Taylor, 1960(Pewhom et al, 2015; I. beddomei Peters, 1880(Masood-Parwees, Nadkarni, 1993; I. glutinosus Linnaeus, 1758; Siphonops annulatus Mikan, 1820 (Sarasin, Sarasin, 1887); Gegeneophis ramaswamii Taylor, 1964 (Beyo et al, 2007)] and derived viviparous species [e.g., Chthonerpeton indistinctum Reinhardt, Lütken, 1862 (Berois, De Sa, 1988); Typhlonectes compressicauda Duméril and Bibron, 1841 ], but an understanding of the morphology, anatomy and function of these reproductive systems still lags behind that of anurans and caudates.…”
Section: Introductionmentioning
confidence: 99%